2010
DOI: 10.1186/1742-2094-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression in oligodendrocytes increases sensitivity to excitotoxic death

Abstract: BackgroundWe previously found that cyclooxygenase 2 (COX-2) was expressed in dying oligodendrocytes at the onset of demyelination in the Theiler's murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD) model of multiple sclerosis (MS) (Carlson et al. J.Neuroimmunology 2006, 149:40). This suggests that COX-2 may contribute to death of oligodendrocytes.ObjectiveThe goal of this study was to examine whether COX-2 contributes to excitotoxic death of oligodendrocytes and potentially contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Specifically, COX-2 was expressed in oligodendrocytes undergoing apoptosis as indicated by immunohistochemistry experiments that found colocalization of the COX-2 protein and the apoptotic mediator caspase-3. These data were confirmed in a further study published in 2010 (16). The latter also showed that COX-2 mediates mechanisms of excitotoxicity against cultured oligodendrocytes (16).…”
Section: Arachidonic Acid Pathway Activation In Animal Models Of Multmentioning
confidence: 52%
See 3 more Smart Citations
“…Specifically, COX-2 was expressed in oligodendrocytes undergoing apoptosis as indicated by immunohistochemistry experiments that found colocalization of the COX-2 protein and the apoptotic mediator caspase-3. These data were confirmed in a further study published in 2010 (16). The latter also showed that COX-2 mediates mechanisms of excitotoxicity against cultured oligodendrocytes (16).…”
Section: Arachidonic Acid Pathway Activation In Animal Models Of Multmentioning
confidence: 52%
“…These data were confirmed in a further study published in 2010 (16). The latter also showed that COX-2 mediates mechanisms of excitotoxicity against cultured oligodendrocytes (16). COX-2 and PGE 2 gene expression were also found in primary cultures of astrocytes from TMEV-infected mice (32).…”
Section: Arachidonic Acid Pathway Activation In Animal Models Of Multmentioning
confidence: 53%
See 2 more Smart Citations
“…In experimental multiple sclerosis models, oligodendrocytes in apoptosis also express increased levels of COX-2 at the demyelination beginning, which seem to make these cells more susceptible to death by glutamate-mediated excitotoxicity [91].…”
Section: Oligodendrocytesmentioning
confidence: 99%